2002
DOI: 10.1159/000063185
|View full text |Cite
|
Sign up to set email alerts
|

Application of Ductus venosus Doppler Velocimetry for the Detection of Fetal Aneuploidy in the First Trimester of Pregnancy

Abstract: Objective: To test the hypothesis the application of ductus venosus Doppler velocimetry may serve as a screening tool between 10 and 14 weeks’ gestation for the detection of fetuses with chromosomal abnormalities. Methods: 372 consecutive fetuses were studied. Based on prior study, a chromosomal abnormality was suspected when either the nuchal translucency was above the 95th centile, or there was reversed or absent flow in the ductus venosus during atrial contraction. Sensitivity, specificity, and the negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
3
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 22 publications
1
45
3
1
Order By: Relevance
“…Our results showed that, despite the findings of previous publications [7,11,13,25,34], DVPI has a poor performance in the prediction of CHD and fetal aneuploidies in fetuses with normal NT.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results showed that, despite the findings of previous publications [7,11,13,25,34], DVPI has a poor performance in the prediction of CHD and fetal aneuploidies in fetuses with normal NT.…”
Section: Discussioncontrasting
confidence: 99%
“…Focusing on this second group, we found different interesting reports: Murtha et al [7] reported that an abnormal DV waveform would detect 93% of chromosomally abnormal fetuses and that 4 of 10 cases with normal NT and abnormal DV waveforms had chromosomal abnormalities. On the basis of their results, they recommended that patients be offered karyotype testing even if the NT is normal, even though other studies did not recommended it.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Also, the addition of PI to NT alone will increase the detection rate from 76 to 85%, and, combined with serum markers, from 88 to 92% (8). Murta et al analyzed absent or reversed flow during atrial contraction in 93.1% of chromosomally abnormal fetuses (32). However, abnormal ductal blood flow was observed in 5.2% of euploid fetuses and 70.8% of fetuses with Tri21 (6).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Recently, several studies have demonstrated an increased impedance to flow in the ductus venosus at the 11 to 13 +6 weeks' scan in DS fetuses. [5][6][7][8][9][10][11][12] Therefore, ductus venosus (DV) Doppler studies could be used to modify the estimated DS risk either selectively in women referred because high-risk for this condition as a secondary screening method, [5][6][7]11,[13][14][15] or incorporated routinely into existing screening protocols as a primary screening method. 6,9,12 Technical difficulties in DV assessment have been postulated as the main limitation to incorporate this marker as a first line screening test to evaluate individual DS risk in combination with NT, although competence in Doppler assessment of the DV can be achieved after extensive supervised training.…”
Section: Introductionmentioning
confidence: 99%